1985
DOI: 10.1210/jcem-60-6-1216
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Forms of Circulating Growth Hormone during Spontaneous Secretory Episodes and in the Basal State*

Abstract: After pharmacological stimulation of the pituitary gland, human GH (hGH) in plasma consists of three or more monomeric molecular forms and several corresponding oligomers. However, the chemical nature of hGH circulating under physiological (stimulated or basal) conditions is not known. In particular, the molecular basis for the GH-like bioactivity of plasma is poorly understood. To gain information on the type(s) of hGH normally found in blood, we extracted hGH from plasma obtained at the time of spontaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…Preliminary data from these 20K-specific assays have confirmed earlier conclusions, from physico-chemical separation, about the proportion of 20K in the circulation [8, 9, 10, 11]. Both 20K and 22K GH appear to be co-secreted in a fixed proportion, and no stimuli favoring secretion of one form versus the other have been identified [8, 9, 10, 11]. …”
Section: Monomeric Human Gh Variantssupporting
confidence: 73%
See 1 more Smart Citation
“…Preliminary data from these 20K-specific assays have confirmed earlier conclusions, from physico-chemical separation, about the proportion of 20K in the circulation [8, 9, 10, 11]. Both 20K and 22K GH appear to be co-secreted in a fixed proportion, and no stimuli favoring secretion of one form versus the other have been identified [8, 9, 10, 11]. …”
Section: Monomeric Human Gh Variantssupporting
confidence: 73%
“…Immunoreactive species that may represent GH fragments have been demonstrated in plasma [10]. This is a highly heterogeneous mixture that varies between plasma samples.…”
Section: Gh Fragments and Degradation Productsmentioning
confidence: 99%
“…CIRCULATING human growth hormone (hGH) consists of several molecular isoforms, in which 22 kilodalton hGH (22K-hGH) is the most abundant [1]. Twenty kilodalton human GH (20K-hGH), a naturally occurring isoform of 22K-hGH, arises from the same gene (hGH-N) as 22K-hGH by alternative splicing of mRNA [2].…”
mentioning
confidence: 99%
“…Recent by PAGE under nondenaturing conditions at pH 7.5 in a disconevidence has shown that in adult man, at least three monomeric tinuous TES-acetate-chloride-Bistris buffer system. Experimental species and several hGH oligomers circulate in blood (3)(4)(5)(6)(7). The details of these procedures have been reported previously (3,15).…”
Section: Page Polyacrylamide Gel Electrophoresismentioning
confidence: 99%